MEASLES PNEUMONIA IN CHILDREN: CLINICAL AND MORPHOLOGICAL FEATURES OF THE COURSE - Nezgoda, I.I.; Havryliuk, A.O.; Asaulenko, A.A.; Kholod, L.P.; Onofriichuk, O.S.; Naumenko, O.M. (World of Medicine and Biology, 2020)
The article presents the results of a retrospective analysis of 96 patients’ histories with measles established, with a detailed course study and the anamnestic data analysis. The measles infection course was accompanied with signs of the intoxication syndrome, the classic catarrhal triad manifestation (coughing, rhinorrhea and conjunctivitis), and the exanthema syndrome. Most of the diseased children are not vaccinated against measles. The patients had a complicated disease course with manifested symptoms of measles pneumonia, as the most common complication in this pathology. Morphological and histological changes of the lungs in children with severe mesles course were characterized by abundant infiltration of both the interalveolar septa and alveolar lumens by polymorphocellular infiltrate, consisting of neutrophilic leukocytes, eosinophils, lympho-histiocytes with numerous parietal hyaline masses (hyaline membranes). There was a giant-cell metaplasia of the alveolar epithelium.
Keywords: measles in children; pneumonia; pathomorphological changes; histological examination